DATA INTEGRITY PROOF (DIP) IN CLOUD STORAGE - Pratik Bhujbal; Anupam Pahnale; Parve Gorakh; Prof. Mohit Dighe (International Journal of Innovations in Engineering Research and Technology, 2021)
Nowadays, Data is rising over internet in terabytes and Exabyte. So, there is a need of storing these data which has been fulfilled by cloud computing. Though the service of cloud appear to be efficient and cost effective. Yet there are some challenges which are faced in cloud computing such as Data security and Authentication. In cloud Storage the data of Owner is stored in cloud where the cloud servers are remotely located the owner of the data does not have any direct control over the data. If the data over cloud is modified by the cloud, Third Party Auditor (TPA) or any other person there is no precision such that the owner of the data gets the information about the modification of the data. TPA is a Third Party Auditor who has